STUDIES ON BRIDLE LENGTH IN ONE BOAT MID WATER TRAWLING. - MHALATHKAR, H N; RAMA RAO, S V. S; MATHAI, P GEORGE (Fishery Technology, 2017)
Investigations on the comparative fi;hing trials to study the eJ!ect of bridles f~r a10.5 m four equal panelled one-boat midwc.ter trawl are descn.bed. Three b~Â·1dlelengths of 20, 30 and 40 m were tested for relative efficiency cvaluatton. 30 m .bndles are found to be more suitable for the particular design and arbitrary selectton of bridle length would be detrimenLtl to the efficiency of nets.